Penugasan Infografis Sebagai Upaya Memupuk Keterampilan 4c Pebelajar - Mokhamad Syaifudin (JKTP: Jurnal Kajian Teknologi Pendidikan, 2021)
4C (Critical thinking, Creativity & Innovation, Collabotion, Communication) is an acronym for a set of 21st century skills to be achieved during learning in today's classes. One way to achieve these skills can be facilitated through a variety of learning experiences provided by teachers in the classroom. One of the learning experiences that can be assigned to students is the assignment to make infographics. An assignment that centers on the creation of attractive visual communication and utilizes current digital technology. The assignment will be very useful to provide nuances of learning variations, especially in the current era of online learning. Many studies have shown the effectiveness of infographics to support students’ learning in the classroom. It is therefore, interesting to discuss here. In this article, a conceptual study of the potential attainment of the four skills above is described theoretically and supported by relevant and actual literature.Abstrak4C (Critical thinking, Creativity & Innovation, Collabotion, Communication) merupakan  keterampilan abad 21 yang hendak dicapai dalam pembelajaran di kelas-kelas dewasa ini. Ketercapaian ketrampilan ini salah satunya dapat difasilitasi melalui variasi pengalaman belajar yang diberikan oleh guru di kelas. Salah satu pengalaman belajar yang bisa diberikan ke peserta didik adalah penugasan membuat infografis. Sebuah bentuk penugasan yang terfokus pada komunikasi visual yang menarik dan memanfaatkan teknologi digital saat ini. Bentuk penugasan yang tentunya akn sangat bermanfaat untuk memberikan nuansa variasi beljar khususnya juga di era pembelajaran daring saat ini. Banyak penelitian yang telah menunjukkan efektiftas infografis untuk mendukung kegiatan pembelajaran di dalam kelas, sehingga menarik untuk di kaji disini.  Pada artikel ini kajian secara konseptual terhadap potensi pencapaian ke empat keterampilan diatas, dijabarkan secara teoretis dan didukung dengan kajian pustaka yang relevan serta aktual.